Incidence and death rate of sarcoidosis in Korea in association with metabolic diseases. Issue 5 (17th January 2022) - Choi, Jin Young; Lee, Joo Hee; Seo, Ji Min; Yun, So Yeon; Koo, Ha Yeh Rin; Yu, Dong Soo; Lee, Young Bok
Abstract: Sarcoidosis is a systemic granulomatous disease that affects a variety of organs. Although the etiology has not been fully understood, it is thought that diverse genetic and environmental factors interact with the immune system to develop granulomas. The incidence and death rate of sarcoidosis vary according to race. This study was conducted to identify the epidemiology of sarcoidosis in Korea and reveal its association with comorbid diseases such as diabetes mellitus, hypertension, and dyslipidemia in a population‐based database. We retrospectively analyzed Korean National Health Insurance claims data between 2006 and 2017. The average annual incidence from 2006 to 2017 was 0.82/100 000 person‐years and the all‐cause death rate in sarcoidosis patients was 9.25/1000 cases. The incidence of sarcoidosis was higher in patients with diabetes mellitus, hypertension, and dyslipidemia than patients without those underlying diseases. Sarcoidosis patients with diabetes mellitus and hypertension showed an increased death rate after adjusting the confounding factors (hazard ratio [95% confidence interval], 1.66 [1.23–2.23] and 1.73 [1.29–2.31] respectively), however, patients with dyslipidemia showed a low death rate (HR = 0.64 [0.46–0.88]). In conclusion, we found that sarcoidosis is associated with diabetes mellitus, hypertension, and dyslipidemia and that diabetes mellitus and hypertension increase the risk of death in sarcoidosis patients. Extra caution is needed in sarcoidosis patients who already have these metabolic diseases.